Implementasi Komunikasi Organisasi Di Satuan Pendidikan Madrasah Aliyah Swasta Kecamatan Medan Area Kota Medan - Cindi Gemilang; Rina Hidayah Tambusai; Carles Harahap; Mesiono Mesiono; Toni Nasution (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to explore the implementation of organizational communication at Madrasah Aliyah Swasta in Medan Area, specifically focusing on communication between the madrasah leadership, teachers, students, and parents. Effective communication in educational institutions is crucial to support the smooth flow of the learning process and achieve educational goals. However, communication challenges include limited access to technology, low parental involvement, and issues with the understanding of the information received. The research method used is qualitative with a case study approach, involving interviews with the madrasah principal, teachers, and parents. The findings show that while internal communication between the madrasah leadership and teachers works relatively well, the main challenge lies in the suboptimal involvement of parents, particularly concerning access to technology such as WhatsApp. Therefore, it is important to enhance parental participation and ensure that the information conveyed can be received evenly by all parties involved in the educational process.